A global perspective on the abundance, diversity and mobility of antibiotic resistance genes in Escherichia coli - Qing, Yun; Zou, Zhongai; Jiang, Guolian; Qin, Lingshi; Liu, Kehui; Liu, Zongbao (Frontiers in Veterinary Science, 2024)
IntroductionEscherichia coli (E. coli), a ubiquitous opportunistic pathogen, poses a growing threat to human health due to the increasing prevalence of antibiotic resistance. However, a comprehensive understanding of the global distribution, diversity, and transmission of antibiotic resistance genes (ARGs) in E. coli remains lacking, hindering effective strategies to combat resistance.MethodsIn this study, we analyzed 94,762 E. coli genome sequences obtained from the NCBI database using advanced bioinformatics tools. ARGs were identified by comparing sequences against a custom ARG database using BLAST. Mobile genetic element (MGE)-associated ARGs were identified by matching with ISfinder databases. Global distribution of ARGs was analyzed by clustering mobile ARG sequences with 99% genetic similarity.ResultsOur analysis revealed that 50.51% of the E. coli genome sequences contained ARGs, totaling 301,317 identified ARG sequences. These ARGs were categorized into 12 major classes and 229 subtypes. Notably, ARGs associated with multi-drug resistance (MDR), β-lactams, macrolide-lincosamide-streptogramins (MLS), tetracyclines, and aminoglycosides were particularly abundant, with the subtypes mdtK, macB, and ampC being especially prevalent. Additionally, significant differences in ARG abundance and diversity were observed across countries, with higher diversity found in high-income nations. Furthermore, 9.28% of the ARG sequences were linked to MGEs, accounting for 98.25% of all ARG subtypes. Notably, 4.20% of mobile ARGs were identified in over 20 countries, with β-lactam and aminoglycoside ARGs being the most widespread.DiscussionThis study provides a comprehensive overview of the global distribution and transmission of ARGs in E. coli. The high abundance of MDR and β-lactam-related ARGs, along with their widespread transmission across countries, highlights the urgent need for global surveillance and control measures. Furthermore, the strong association between ARGs and MGEs underscores the role of horizontal gene transfer in the spread of resistance. The observed variations in ARG diversity between countries suggest that socioeconomic factors, such as healthcare infrastructure and antibiotic usage patterns, significantly influence ARG prevalence. These findings are crucial for informing global strategies to mitigate the spread of antibiotic resistance and improve public health outcomes.